Types of Code Switching Used in Merry Riana’s Podcast Entitled Kata Marissa Anita Tentang Insecure & Depresi Karena Social Media - Nyoman Cindy Marantika Dewi,; I Made Suastra,; Made Detriasmita Saientisna, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
the phenomena of code switching has became more frequent, especially in Indonesia which has a lot of different communities with their respective languages. this study was conducted in order to enhance the knowledge regarding code switching by analyzing the types of code switching used in the podcast chosen. Podcast taken form Marry Riana entitled Kata Marissa Anita tentang Insecure & Depresi karena Social Media was used in this study as data source. Qualitative method was used as method in conducting the research by doing documentation, and observation method in analyzing the data with the help of checklist as its instrument. The data analyzed were the form of written data which was got by transcribing the utterances in the podcast. Based on the analysis, three types of code switching proposed by Hamers and Blanc (2003) was used in the podcast. The types of code switching used by Marissa Anita, and Mary Riana in the podcast were inter-sentential code switching, intra-sentential code switching, and extra-sentential code switching.